SISTEM STERILISASI AIR MINUM ISI ULANG PADA DEPOT AIR MINUM ISI ULANG (DAMIU) DI KOTA DAN KABUPATEN PEKALONGAN - Nila Oktaviani; Siska Rusmalina (LPPM Universitas Pekalongan, 2015)
In this time, most society have the solid activity, so that society tend to to chosen the way of more practical with the expense which cheaper relative in fulfilling amount of water required drink the nya that is by using drinking water refill (Sulityandari, 2009). Water consumed shall fulfill the good water quality, for that observation to irrigate refill to utilize to protect consumer. Research to know whether system of sterilization of drinking water refill (DAMIU) in Town and Regency Pekalongan yield the water which with quality and competent to be consumed.Research diskriptif to see the system of sterilization of drinking water refill ( DAMIU) in Town and Pekalongan Regency yield the water which with quality and can be consumed by conducting test of cemaran of bacterium Colioform. Sampel Research use 37 DAMIU which is gone the round of Town and Regency Pekalongan enlisted by and also not yet been enlisted in DINKES Town and or Regency Pekalongan.Result of research region of subdistrict Wiradesa 5 from 12 sampel give the impure result which are positive by bacterium Colioform. Result of test DAMIU region of subdistrict of North Pekalongan 5 from 13 impure sampel by bacterium Colioform. Result of test DAMIU region of subdistrict of East Pekalongan 6 from 12 impure sampel by bacterium Colioform. All DAMIU which used as sampel have opened enlisted Public Health Service of Pekalongan town and also regency and a Quality inspection irrigate.Keywords: Sterilization system, town or Bat regency.